Pengaruh Dana Pihak Ketiga (DPK), Capital Adequacy Ratio (CAR), Non Perfoning Financing (NPF) dan Return On Asset (ROA) Terhadap Pembiayaan Murābaḥah - Muhajir muhajir (Prodi Hukum Keluarga Fakultas Agama Islam Universitas Nurul Jadid, 2020)
This research discusses the effect of third party funds (DPK), capital adequacy ratio (CAR), non-preponing financing (NPF) and returns on assets (ROA) on Murābaḥah financing in banking, given the important role of banking in the wheels of the economy, one of which is as an institution. intermediation whose task is to collect funds from the public and channel them back in the form of credit. This study aims to determine the factors that affect the distribution of Murābaḥah Financing at Bank Syariah Mandiri and to determine the extent of the relationship between Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Non-Performing Finance (NPF), and Return On Assets (ROA) towards Murābaḥah Financing at Bank Syariah Mandiri in 2016-2019. The sample used in this study was the 2016-2019 Bank Syariah Mandiri Quarterly Financial Report using the purposive sampling method. The type of data used is secondary data obtained from published financial reports and downloaded through the official website of Bank Syariah Mandiri. The analytical method used is multiple regression with a significance level of 5%. The results of the analysis show that partially only DPK and NPF have a significant positive effect on Murābahah Financing, while CAR and ROA do not affect Murābaḥah Financing. Simultaneously, the variables of DPK, CAR, NPF, and ROA have a significant effect on Murābaḥah Financing. This is evidenced by the sig-F value of 0.002 which is smaller than the 5% significance.